The Concept of Shura in Islamic Governance Practice of Shura during the Caliph Umar Bin Khattab - Sucilawati Sucilawati (The International Journal of Politics and Sociology Research, 2020)
Shura is one of the political conceptions among the conceptions whose roots are firmly rooted in the midst of Islamic society, and become a feature of the Islamic government system from government systems other than Islam. Shura has maintained its existence in Islamic political life, to strengthen the relationship between the rulers and their people, in the form of continuous reference to the rulers to the people to produce political decisions that are in the interest of the wider community, which depart from awareness, maturity and understanding, and to make great power on humans is close to the idea of ​​general principles for Muslims. Shura is not only applied in the government system. But also implemented in the order of everyday life. For example, deliberation applied in family, work, social, economy as well as in society. deliberation is also a clear proof of respect for human reason; which we can see is a proof of God's glorification to humans, therefore deliberation can provide a benefit; and with deliberation can also produce a solution. And with deliberation also everyone will have the same opportunity without distinction, everyone is free to express opinions. Moreover, in terms of determining the leader of the people, deliberation has an important role in that regard. The practice of shura applied by Umar bin Khattab during the reign of that time became a role model for the people in the next period. The Shura Council formed by Umar became a concept that was not only applied in the government system at that time, but also practiced in social activities and government systems in Islamic countries to this day. The practice of shura during the reign of the caliphate of Umar bin Khattab became the forerunner to the institutional implementation of the concept of shura in the political history of Muslims. For this reason, tracing the practice of shura during the reign of Umar is an interesting study to discuss in the midst of the existing political dynamics.